2015
DOI: 10.1586/14737159.2015.1113132
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of next generation sequencing to epilepsy genetics

Abstract: During the last decade, next generation sequencing technologies such as targeted gene panels, whole exome sequencing and whole genome sequencing have led to an explosion of gene identifications in monogenic epilepsies including both familial epilepsies and severe epilepsies, often referred to as epileptic encephalopathies. The increased knowledge about causative genetic variants has had a major impact on diagnosis of genetic epilepsies and has already been translated into treatment recommendations for a few ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 63 publications
2
51
1
7
Order By: Relevance
“…We systematically screened all exons and exon‐intron boundaries of SCN8A in a cohort of 1095 unselected patients with various forms of epilepsy using different next generation sequencing (NGS) panels . The panels included from 45 to 500+ genes related to epilepsy, intellectual disability, or autism.…”
Section: Methodsmentioning
confidence: 99%
“…We systematically screened all exons and exon‐intron boundaries of SCN8A in a cohort of 1095 unselected patients with various forms of epilepsy using different next generation sequencing (NGS) panels . The panels included from 45 to 500+ genes related to epilepsy, intellectual disability, or autism.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the use of highthroughput approaches to sequence DNA is revealing a landscape of mutations in genetic epilepsies, affecting a variety of genes involved in neuronal excitability, synaptic transmission, neuronal metabolism, or network development. [6,7] Thus, mutations of protocadherin delta-2 subclass of the cadherin super family (PCDH19), Aristalessrelated homeobox, cyclin-dependent, kinase-like 5, and syntaxin-binding protein 1 genes have been identified in monogenic epilepsies without brain malformations that often manifest as severe forms, with features of epileptic encephalopathy, often having early seizure onset and developmental delay, even if with diverse and distinctive phenotypes. [6,7] Other examples are mutations of the LGI1 gene (leucine-rich, glioma-inactivated 1) that have been associated to autosomal dominant temporal lobe epilepsy, a form of focal epilepsy associated to auditory symptoms and audiogenic seizures.…”
Section: Main Molecular Mechanisms Of Epileptogenesismentioning
confidence: 99%
“…[6,7] Thus, mutations of protocadherin delta-2 subclass of the cadherin super family (PCDH19), Aristalessrelated homeobox, cyclin-dependent, kinase-like 5, and syntaxin-binding protein 1 genes have been identified in monogenic epilepsies without brain malformations that often manifest as severe forms, with features of epileptic encephalopathy, often having early seizure onset and developmental delay, even if with diverse and distinctive phenotypes. [6,7] Other examples are mutations of the LGI1 gene (leucine-rich, glioma-inactivated 1) that have been associated to autosomal dominant temporal lobe epilepsy, a form of focal epilepsy associated to auditory symptoms and audiogenic seizures. [9] In addition, recent studies have identified some families presenting with familial focal epilepsy with variable foci mutations in Dishevelled, Egl-10, and Pleckstrin domain-containing (DEPDC5) protein, whose function is still unclear but might be involved in membrane trafficking, G protein signaling, and/or modulation of the mTOR complex 1.…”
Section: Main Molecular Mechanisms Of Epileptogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…1 Early genetic diagnosis is critical for prognostic assessment, genetic counseling, and, in some cases, personalized treatment attempts. 1 Early genetic diagnosis is critical for prognostic assessment, genetic counseling, and, in some cases, personalized treatment attempts.…”
Section: Introductionmentioning
confidence: 99%